Cervarix - Preventing cervical cancer and other diseases related to HPV - Chambers, S; Kassianos, G; Brown, P; Gaw, A; Kirby, M; Morrell, J; Schachter, M; Tamargo, J; Yawn, B; Yawn, R; Barakat, K; Dalrymple, J; et al. (2008)
Human papillomavirus (HPV) is the pathological agent required for the development and progression of precancerous lesions in the cervical epithelium. Just two HPV types account for around 70% of all cases of cervical cancer. Therefore, there is a clear rationale for the development of prophylactic vaccines that protect against infection by these oncogenic HPV strains in order that the substantial burden of cervical cancer can be reduced. Two vaccines have been developed which comprise type-specific virus-like particles (VLPs) of the L1 capsid protein produced in recombinant expression systems. These VLPs are structurally similar to the native virus, but as they contain no viral DNA, they are non-infectious and non-oncogenic. Cervarix is a bivalent vaccine, which targets the two HPV typed (HPV 16 and 18) responsible for the majority of cervical cancers. Clinical trials have shown that Cervarix, formulated with a proprietary adjuvant (ASO4), stimulates a robust immune response in vaccinated women, such that virtually all vaccinees seroconvert within 1 month of completing the vaccine schedule. High titres of type-specific antibodies lead to a significant reduction in the number of incident and persistent HPV 16 and 18 infections. Clinically, this manifests as a reduction in the incidence of pre-cancerous cervical lesions. Cervarix has no efficacy in clearing pre-existing HPV infections, but should continue to protect against infection by the remaining vaccine type to which women have not been exposed. The vaccine has a favourable safety profile, with localised injection-site reactions the most common adverse event. The introduction of Cervarix has the potential to substantially reduce the burden of HPV infection, and thus reduce the morbidity, mortality and socioeconomic burden associated with cervical cancer. © 2008 CSF Medical Communications Ltd.